QARAQALPAQ XALÍQ DÁSTANLARÍNDA TÚS MOTIVINIŃ PAYDA BOLÍWÍ HÁM GENEZISI - Kulımbetova, A.K. (SCIENCE and SOCIETY, 2025)
This article analyzes the emergence and genesis of the dream motif in Karakalpak folk epics. The study examines the mythological, religious, and historical roots of the dream motif and reveals its role in the development of the plot of dastans. The research results show the peculiaritiyes of the dream motif in Karakalpak folk epics and its connection with the worldviyew and beliyefs of the people.